2021
DOI: 10.3390/molecules26134081
|View full text |Cite
|
Sign up to set email alerts
|

The Fruits of Paris polyphylla Inhibit Colorectal Cancer Cell Migration Induced by Fusobacterium nucleatum-Derived Extracellular Vesicles

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. Gut microbiota are highly associated with CRC, and Fusobacterium nucleatum was found to be enriched in CRC lesions and correlated with CRC carcinogenesis and metastases. Paris polyphylla is a well-known herbal medicine that showed anticancer activity. The present study demonstrates that P. polyphylla inhibited the growth of CRC cells. In addition, treating with active compounds pennogenin 3-O-beta-chacotrioside and polyphyllin VI isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The next step is to modify the effects of Fusobacterium nucleatum to improve patient outcomes. A first study addressed this goal and demonstrated that Paris polyphyla, a herbal medicine, could inhibit both colorectal-cancer and Fusobacterium nucleatum growth in human colorectal-cancer cell lines [51].…”
Section: Complications During Chemo-and Immunotherapymentioning
confidence: 99%
“…The next step is to modify the effects of Fusobacterium nucleatum to improve patient outcomes. A first study addressed this goal and demonstrated that Paris polyphyla, a herbal medicine, could inhibit both colorectal-cancer and Fusobacterium nucleatum growth in human colorectal-cancer cell lines [51].…”
Section: Complications During Chemo-and Immunotherapymentioning
confidence: 99%
“…Studies have shown that the root extract of Rhizoma Paridis has obvious inhibitory effects on lung cancer, gastric cancer, colon cancer, and breast cancer (You et al, 2021). Other studies have also shown that the fruit and aerial parts of Rhizoma Paridis have the effects of inhibiting the migration of cancer cells (Qin et al, 2018;Lin et al, 2021).…”
Section: Application Of Rhizoma Paridis and Research On Its Active In...mentioning
confidence: 99%
“…Unknown; 3. TLR2 25 , 105–107 Lacticaseibacillus paracasei Unknown Inhibit colon cancer development. PDK1/AKT/Bcl-2 108 Lactobacillus plantarum Unknown Up-regulate the expression of host defense genes to provide protection for the host Unknown 89 Lactobacillus reuteri Glucosyltransferase, serine protease and elongation factor Tu Enhancing immunomodulatory cell-mediated immunosuppression by activating macrophages to inhibit Th1 and Th17-mediated inflammatory responses Unknown 109 Pediococcus pentosaceus Unknown Promote that M2-type polarization of macrophages TLR2 110 Propionibacterium freudenreichii CIRM-BIA 129 SlpB Modulate inflammatory responses NF-κB 87 Pseudomonas aeruginosa Unknown Induces mitochondrial dysfunction in macrophages and inhibits host protein synthesis, ultimately inducing an inflammatory response Unknown 111 Salmonella Typhimurium ATCC 14028 Unknown Inhibit colon cancer development Unknown 112 Vibrio cholerae O395 Unknown Activate innate immune response of host NOD1 113 Notes: DCs, dendritic cells; HFD, high-fat diet; GBPs, guanylate-binding proteins; MAMPs, microbe-associated molecular patterns; MINPP, mamma...…”
Section: Gbevs-mediated Bacteria-host Interactionsmentioning
confidence: 99%
“…Tai et al co-cultured F. nucleatum EVs with Caco-2 cells and found that it promotes mitochondrial fusion and invasiveness in cells, while the use of Paris polyphylla , an herb, inhibits the spread of colon cancer. 105 Using enzyme-linked immunosorbent assay (ELISA), Lamprinaki et al determined that LPS-loaded F. nucleatum ssp. animalis EVs could bind to sialic acid-binding immunoglobulin-like lectins-7, which are abundant on innate immune cells and tumor infiltrating T cells and inhibit immune activation upon binding to LPS, and GBEVs induced TNF-α production by human monocyte-DCs, thereby creating a pro-inflammatory environment to promote colon cancer development.…”
Section: Gbevs-mediated Bacteria-host Interactionsmentioning
confidence: 99%